(sinx)^{p-1}(cosx)^{-p}/(acosx+bsinx)[0,π/2]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{p-1}(\cos x)^{-p}}{a \cos x+b \sin x}dx=\frac{π\csc pπ}{a^{1-p}b^p}  (0 \lt p \lt 1 )\\
&(2)  \displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{-p}(\cos x)^{p-1}}{a \sin x+b \cos x}dx=\frac{π\csc pπ}{a^{1-p}b^p}  (0 \lt p \lt 1 )\\
&(3)  \displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{1-p} (\cos x)^p}{(\sin x+\cos x)^3}dx=\frac{p(1-p)}{2}π\csc pπ  (-1 \lt p \lt 2 )\\
&(4)  \displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{p} (\cos x)^{1-p}}{(\sin x+\cos x)^3}dx=\frac{p(1-p)}{2}π\csc pπ  (-1 \lt p \lt 2 )\\
\end{alignat}ただし、全て \(a,b \gt 0\)











<証明>

\((1)\) \(\tan x=t\) と置きます。\(\displaystyle \left(\frac{1}{\cos^2 x}dx=dt\right)\)
\begin{alignat}{2}
&  \displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{p-1}(\cos x)^{-p}}{a \cos x+b \sin x}dx=\displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{p-1}(\cos x)^{1-p}}{(a \cos x+b \sin x)\cos x}dx\\
&=\displaystyle\int_0^{\frac{π}{2}} \frac{(\tan x)^{p-1}}{a+b \tan x} \cdot \frac{1}{\cos^2 x}dx=\displaystyle\int_0^{\infty} \frac{t^{p-1}}{a+bt}dt
\end{alignat}\(bt=as\) と置きます。\((bdt=ads)\)
\begin{alignat}{2}
&=\displaystyle\int_0^{\infty} \frac{\left(\frac{a}{b}s\right)^{p-1}}{a+as} \cdot \frac{a}{b}ds=\frac{a^{p-1}}{b^p}\displaystyle\int_0^{\infty} \frac{s^{p-1}}{1+s}ds\\
&=\frac{a^{p-1}}{b^p} \cdot \frac{π}{\sin pπ}=\frac{π\csc pπ}{a^{1-p}b^p}
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{p-1}(\cos x)^{-p}}{a \cos x+b \sin x}dx=\frac{π\csc pπ}{a^{1-p}b^p}$$







\((2)\) \(\cot x=t\) と置きます。\(\displaystyle \left(-\frac{1}{\sin^2 x}dx=dt\right)\)
\begin{alignat}{2}
&  \displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{-p}(\cos x)^{p-1}}{a \sin x+b \cos x}dx=\displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{1-p}(\cos x)^{p-1}}{(a \sin x+b \cos x)\sin x}dx\\
&=\displaystyle\int_0^{\frac{π}{2}} \frac{(\cot x)^{p-1}}{a+b \cot x} \cdot \frac{1}{\sin^2 x}dx=\displaystyle\int_{\infty}^0 \frac{t^{p-1}}{a+bt}(-dt)=\displaystyle\int_0^{\infty} \frac{t^{p-1}}{a+bt}dt=\frac{π\csc pπ}{a^{1-p}b^p}\\
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{2}} \frac{(\sin x)^{-p}(\cos x)^{p-1}}{a \sin x+b \cos x}dx=\frac{π\csc pπ}{a^{1-p}b^p}$$







\((3)\) \(\cot x=t\) と置きます。\(\displaystyle \left(-\frac{1}{\sin^2 x}dx=dt\right)\)
\begin{alignat}{2}
\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{1-p} (\cos x)^p}{(\sin x+\cos x)^3}dx&=\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{-p} (\cos x)^p \cdot \sin x}{(\sin x+\cos x)^3}dx\\
&=\displaystyle\int_0^{\frac{π}{2}}\frac{(\cot x)^p}{(1+\cot x)^3} \cdot \frac{1}{\sin^2 x}dx\\
&=\displaystyle\int_{\infty}^0 \frac{t^p}{(1+t)^3}(-dt)=\displaystyle\int_0^{\infty} \frac{t^p}{(1+t)^3}dt\\
&=B(p+1,2-p)=\frac{Γ(p+1)Γ(2-p)}{Γ(3)}\\
&=\frac{pΓ(p)(1-p)Γ(1-p)}{2}=\frac{p(1-p)}{2} Γ(p)Γ(1-p)\\
&=\frac{p(1-p)}{2} \cdot \frac{π}{\sin pπ}=\frac{p(1-p)}{2}π\csc pπ
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{1-p} (\cos x)^p}{(\sin x+\cos x)^3}dx=\frac{p(1-p)}{2}π\csc pπ$$







\((4)\) \(\tan x=t\) と置きます。\(\displaystyle \left(\frac{1}{\cos^2 x}dx=dt\right)\)
\begin{alignat}{2}
\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{p} (\cos x)^{1-p}}{(\sin x+\cos x)^3}dx&=\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{p} (\cos x)^{-p} \cdot \cos x}{(\sin x+\cos x)^3}dx\\
&=\displaystyle\int_0^{\frac{π}{2}}\frac{(\tan x)^p}{(\tan x+1)^3} \cdot \frac{1}{\cos^2 x}dx\\
&=\displaystyle\int_0^{\infty} \frac{t^p}{(t+1)^3}dt=\frac{p(1-p)}{2}π\csc pπ
\end{alignat}以上より$$\displaystyle\int_0^{\frac{π}{2}}\frac{(\sin x)^{p} (\cos x)^{1-p}}{(\sin x+\cos x)^3}dx=\frac{p(1-p)}{2}π\csc pπ$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です